Alteration of neuromuscular function in squash - Girard, O.; Micallef, J. P.; Noual, J.; Millet, G. P. (Journal of Science and Medicine in Sport, 2010)
The alteration in neuromuscular function of knee extensor muscles was characterised after a squash match in 10 trained players. Maximal voluntary contraction (MVC) and surface EMG activity of vastus lateralis (VL) and vastus medialis (VM) muscles were measured before and immediately after a 1-h squash match. M-wave and twitch contractile properties were analysed following single stimuli. MVC declined (280.5 ± 46.8 vs. 233.6 ± 35.4 N m, -16%; P < 0.001) after the exercise and this was accompanied by an impairment of central activation, as attested by decline in voluntary activation (76.7 ± 10.4 vs. 71.3 ± 9.6%, -7%; P < 0.05) and raw EMG activity of the two vastii (-17%; P < 0.05), whereas RMS/M decrease was lesser (VL: -5%; NS and VM: -12%; P = 0.10). In the fatigued state, no significant changes in M-wave amplitude (VL: -9%; VM: -5%) or duration were observed. Following exercise, the single twitch was characterised by lower peak torque (-20%; P < 0.001) as well as shorter half-relaxation time (-13%; P < 0.001) and reduced maximal rate of twitch tension development (-23%; P < 0.001) and relaxation (-17%; P < 0.05). A 1-h squash match play caused peripheral fatigue by impairing excitation-contraction coupling, whereas sarcolemmal excitability seems well preserved. Our results also emphasise the role of central activation failure as a possible mechanism contributing to the torque loss observed in knee extensors. Physical conditioners should consider these effects when defining their training programs for squash players.